i860™ microprocessor architecture. - Margulis, Neal (Berkeley, California, United Stadtes of America : McGraw-Hill, Inc., 1990)
"This book is written to help you understand the i860 microprocessor. As a new generation of computers that utilize the ¡860 microprocessor enters the market, new opportunities are created. There are hundreds, if not thousands, of applications awaiting the power and capabilities of the i860 processor. This book will aid you in several ways. First, it will give you valuable insights into the i860 architecture that will help you to understand the capabilities of the i860 microprocessor. Next, this book will guide you in programming your first power-packed i860 microprocessor application. Finally, this book provides the most complete reference section on i860 microprocessor instructions available anywhere. This reference, in itself, will make programming the i860 microprocessor much easier and faster. Throughout the text, isolated code fragments and more extensive application program examples reinforce programming concepts and give you a cornerstone on which to build your application." (Copied from about this book).
Acknowledgement. Foreword. Introduction. Why this book is for you. Chapter 1. i860 Microprocessor overview. Chapter 2. Processor design: A performance-driven approach. Chapter 3. i860 microprocessor architecture overview. Chapter 4. Machine organization. Chapter 5. RISC core operations. Chapter 6. Floating-point operations. Chapter 7. Graphics rendering instructions. Chapter 8. Programming for parallelism. Chapter 9. Operating system support. Chapter 10. Applications example: the fast fourier transform. Chapter 11. Application example: the 3-D graphics transform. Appendix A. Instructions set summary. Appendix B. Instruction format and encoding. Appendix C. Instructions timing and characteristics. Index.
Keywords: INTEL I860 -- MICROPROCESSOR; APLICATION SOFTWARE; BANDWIDTH; COMMUNICATION SYSTEM CONTROL; DATA BUSES; INNOVATION MANAGEMENT